Pengembangan E-Book Materi Jual Beli dengan Realistic Mathematics Education Berbasis Kearifan Lokal Suku Dayak Kalimantan Tengah - Rezki, Istighfaris; Sari, Rospala Hanisah Yukti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to: 1) To find out whether e-book buying and selling material using a Realistic Mathematics Education approach based on local Dayak wisdom can meet valid criteria; 2) To find out whether the e-book buying and selling material using the Realistic Mathematics Education approach based on local Dayak wisdom can meet the criteria for being suitable for use. The research method used is Research and Development (RnD) with a 4-D model developed by Thiagarajan. The data collection technique is a Likert Scale to determine whether the product being developed meets feasibility. The results of the research show that 1) the e-book buying and selling material using the Realistic Mathematics Education approach based on the local wisdom of the Dayak Tribe has met the valid criteria; 2) e-book buying and selling material with a Realistic Mathematics Education approach based on local Dayak wisdom has met the criteria for being suitable for use. The conclusions from this research are: 1) e-book buying and selling material using a Realistic Mathematics Education approach based on local Dayak wisdom has met the valid criteria; 2) e-book buying and selling material with a Realistic Mathematics Education approach based on local Dayak wisdom has met the criteria for being suitable for use. Keywords: Barter System, E-Book, Economy, Local Wisdom, Realistic Mathematics Approach